Three-dimensional geomagnetic field effects on a plasma thruster plume expansion. (October 2020) - Cichocki, F.; Merino, M.; Ahedo, E.
Abstract: A 3D hybrid particle-in-cell code with a partially-magnetized fluid electron model is presented and applied to study the effects of a uniform external geomagnetic field on an expanding plasma thruster plume at three different angles. Electron currents are governed by both the magnetic field and collisional effects with the heavy ions and neutrals. While an axial magnetic field (parallel to the plume axis) induces azimuthal electric currents and an observable plume channeling, an oblique field produces non-trivial asymmetric deformations of the plume cross-section, and induces axial-radial electric current loops. A center of mass analysis of the plasma plume demonstrates that the electron response produces an electric field that balances the Lorentz force deflection on the ions, so that no net plume momentum deflection is observed.